2022
DOI: 10.1111/apa.16490
|View full text |Cite
|
Sign up to set email alerts
|

Incremental costs of scaling up kangaroo mother care: Results from implementation research in Ethiopia and India

Abstract: Aim To estimate incremental costs of an implementation model for scaling up Kangaroo Mother Care (KMC) for neonates with birthweight <2000 g. Methods Seven sites across Ethiopia and India collected data for 2018–19 to calculate incremental recurrent costs (of health worker time, supplies, and operations) and start‐up costs for KMC scale up. The costs were estimated per live newborn <2000 g eligible for KMC identified in the study population. Results Scaling up KMC in study districts required average incrementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In order to promote the incorporation of KMC into the routine clinical practice for preterm and low birth weight babies, the service cost and health insurance payment system must be optimised. A study found that the major cost driver of KMC is human resources, followed by training and supplies [ 34 ]. Considering the inadequacy of the present scope of health insurance and KMC cost-sharing mechanism, we recommend the government adjusting medical insurance coverage to better reflect the labour costs, investing in initial and recurrent KMC training for medical staff and providing assistance to the necessary hospital facility reforms.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote the incorporation of KMC into the routine clinical practice for preterm and low birth weight babies, the service cost and health insurance payment system must be optimised. A study found that the major cost driver of KMC is human resources, followed by training and supplies [ 34 ]. Considering the inadequacy of the present scope of health insurance and KMC cost-sharing mechanism, we recommend the government adjusting medical insurance coverage to better reflect the labour costs, investing in initial and recurrent KMC training for medical staff and providing assistance to the necessary hospital facility reforms.…”
Section: Discussionmentioning
confidence: 99%